Study on core germplasm construction strategy based on phenotypic traits of wood Pinus yunnanensis - LI Hua; FU Puyan; YAN Xi; CAO Zilin; WANG Xiaoli (Xibei zhiwu xuebao, 2024)
Abstract [Objective] This study aims to construct a reliable core germplasm of Pinus yunnanensis for timber wood, to enhance its breeding, development, and utilization, and to solve the problems of its distribution, high preservation cost, preservation difficulties, and hence promoting its utilization. [Methods] The original germplasm was derived from 780 sample plants of 26 natural P . yunnanensis populations, with 18 phenotypic traits serving as the original data. The study employed two distinct construction strategies, geographical perspective and an enhanced minimum distance stepwise sampling method, to assess the representativeness of the core germplasm constructed with different strategies. [Results] (1) The genetic diversity index of the germplasm subset, including 219 samples constructed from a geographical perspective, was significantly lower than that of the four subsets constructed by the enhanced minimum distance stepwise sampling method; however, it was slightly higher than the original germplasm. The germplasm subset and the original germplasm had MD value of 3.921%, VD value of 83.333%, CR value of 82.207%, and VR value of 99.482%. A principal component analysis of the original germplasm quality and the germplasm subset 18 traits revealed cumulative contribution rates of 79.376% and 82.163%, respectively; the germplasm subset distribution was relatively concentrated. (2) The enhanced minimum distance stepwise sampling method was utilized to construct four seed subsets with sampling ratios of 10%, 20%, 30%, and 40%. Among these, the germplasm subset with a 20% sampling ratio proved to be the most effective, with a diversity index significantly higher than the original germplasm. The germplasm subset with 20% sampling proportion and the original germplasm had MD value of 6.363%, VD value of 83.333%, CR value of 91.099%, and VR value of 124.448%. A principal component analysis was conducted on a germplasm subset with a 20% sampling proportion, revealing a cumulative contribution rate of 83.539%, exceeding that of the original germplasm. The germplasm subset distribution range encompassed the entire sampling range. [Conclusion] Construction using different methods yield varying degrees of genetic diversity from the original germplasm, while both construction methods could represent the core collection of P . yunnanensis germplasm resources. The germplasm subset derived from the geographical perspective offers more advantages in collection, preservation, and renewal of these resources, which provided a method for the preservation of P . yunnanensis germplasm resources and the breeding of superior germplasm, offering a novel reference method for the construction of other germplasm resources.